Problems and Prospects of Modern Inclusive Higher Technical Education in Russia: a View of Future Engineers, Economists and Managers - V. Zerniy, Yu.; B. Nadtochiy, Yu. (International Journal of Engineering and Technology, 2018)
At present time, there are various problems of modern inclusive technical education, consisting the rapid development of modern technologies (their appearance is much faster than the existing timeline for training specialists), high competition (now high-tech and high-tech projects are preferred), and the complexity of training combined with many teachers from real practice, and at the same time unwillingness to go to work, given the relatively low wages.The present article provides an analysis of the problems of modern inclusive technical education identified in Russia through a survey of students and  also suggests ways to solve them.